Pigment Epithelium-Derived Factor-Loaded PEGylated Nanoparticles as a New Antiangiogenic Therapy for Neovascularization. (22nd April 2022) - Zhao, Feng; Fei, Wenlei; Li, Zhouyue; Yu, Hanyang; Xi, Lei
Abstract : Background . Pathological neovascularization, which involves a disruption in the balance between angiogenic and antiangiogenic factors under pathological conditions, is the basis of many intraocular diseases. Pigment epithelium-derived factor (PEDF) is a potent natural, endogenous inhibitor of neovascularization because of its antiangiogenic and neuroprotective benefits. However, its application is restricted by its instability and short half-life. The present study is aimed at investigating the cytotoxicity and antiangiogenic effects of PEDF-loaded PEGylated nanoparticles (NP-PEG-PEDF) on high glucose-stimulated human umbilical vein endothelial cells (HUVECs). Methods . In this study, NP-PEG-PEDF were fabricated using the multiple emulsion method for the first time. HUVECs were cultured in a high concentration of glucose (30 mmol/L D-glucose), simulating diabetic conditions. The antiangiogenic effects of vascular endothelial growth factor (VEGF), pure PEDF, and NP-PEG-PEDF on proliferation, migration, and tube formation were evaluated. VEGF secretion in high glucose-stimulated HUVECs was further tested in vitro. Results . NP-PEG-PEDF exhibited low cytotoxicity in HUVECs. Our results indicated that in vitro, NP-PEG-PEDF attenuated diabetes-induced HUVEC proliferation, migration, and tube formation and suppressed VEGF secretion. The apoptosis of diabetes-induced HUVECs occurred in a dose-dependent manner, which showed a statistically significant difference compared with the PEDF treatment group. Conclusion . Our study is the first to demonstrate that NP-PEG-PEDF exert antiangiogenic effects on high glucose-stimulated HUVECs and have the potential to alleviate microvascular dysfunction. These data suggest that the NP-PEG-PEDF delivery system may offer an innovative therapeutic strategy for preventing neovascularization of the fundus.